Análise de marcadores precoces de doença cardiovascular em pacientes com diabetes tipo 1 no Maranhão - REIS, Roberta Maria Duailibe Ferreira (2020)
INTRODUCTION: Patients with type 1 diabetes (DM1) have a risk of up to four times higher risk of developing cardiovascular disease (CVD), which is the leading cause of death in this population. The aim of this study was to identify and compare early CVD markers in patients with DM1 in the state of Maranhão from August 2018 to October 2019 and relate them to risk factors for CVD, microvascular complications and c peptide values. METHODOLOGY: Patients underwent a clinical-demographic survey, laboratory and cardiovascular tests - Brachial ankle index (ITB), electrocardiogram (ECG), calcium score (EC) and carotid doppler. RESULTS: We evaluated 83 patients with DM1 with a mean of 28 years of age and 14 years of duration of DM1. The prevalence of changes in early CVD markers was: PCRus 54.89%, ITB 21.68%, ECG 12.05%, EC 6.02% and Carotid Doppler 4.81%. There was significant agreement between EC and carotid doppler and these correlated with risk factors of CVD. CONCLUSION: ITB was useful in early identification of CVD in asymptomatic young patients with DM1 and with little disease time. Although EC and carotid doppler are noninvasive tests, carotid doppler has a better cost benefit, and both have limitations in cvD screening in young patients with little duration of DM1. PCRus was the test with the highest prevalence of alterations, but with limited evidence in the identification of subclinical disease in DM1. ECG was not useful in early detection of CVD in this population.